Implementation of Policy for Transforming Unproductive Land into Productive Land in North Tapanuli Regency, North Sumatera Province - Situmorang, Sasma Hamonangan; Simangunsong, Fernandes; Mariani, Dedeh; Indrayani, Etin (Journal of Humanities and Social Sciences Studies, 2025)
North Tapanuli Regency is a major food-producing area in North Sumatra Province, but it still has a considerable amount of idle land. Through North Tapanuli Regency Regulation No. 23 of 2016, the local government is striving to convert idle land into productive land. However, the implementation of this policy still faces various challenges, such as unmet needs of target groups, uneven policy implementation, and limited resources. This study aims to identify, analyze, and explain the implementation of the policy, the determinants of success and failure, efforts to address failures, and the novelty of the policy implementation for converting idle land into productive land in Tapanuli Utara Regency. This study uses Hamdi’s policy implementation theory, namely productivity, linearity, and efficiency. The determining factors that influence the success and failure of policy implementation consist of policy substance, the behavior of implementing officers, work network interactions, target group participation, and resources. The research method used was qualitative with a descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation. The results of the study indicate that policy implementation has not been fully productive, linear, or efficient. The main obstacles are lengthy procedures and the application of policies that are still based on priority areas. As a new development, this study recommends the need for more detailed regulations through a Regional Regulation on the Conversion of Fallow Land into Productive Land so that implementation can be more optimal and equitable.